2014
DOI: 10.1177/0265407513517808
|View full text |Cite
|
Sign up to set email alerts
|

By-gender risk paths of parental psychological control effects on emerging adult overt and relational aggression

Abstract: We modeled by-gender risk paths of maternal, paternal, and parental psychological control effects on emerging adult overt and peer relational aggression using structural equation models. The effect of adolescent conduct problems on emerging adults’ (aged 18–24) aggression was examined through its effect on parents’ psychological control. Additionally, a social–cognitive mediation model of aggression was tested linking conduct problems and parents’ psychological control with hostility and low guilt and concern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
(119 reference statements)
1
8
0
Order By: Relevance
“…Although the vast majority of research in the area is predominantly focused on maternal parenting style (Cabrera, Tamis-LeMonda, Bradley, Hofferth, & Lamb, 2000;Simons & Conger, 2007) current results are in line with several studies which found that paternal but not maternal authoritarian parenting practices including psychological control are linked to increased relational aggression in children (Nelson & Crick, 2002;Nelson, Hart, Yang, Olsen, & Jin, 2006) and to relational and overt aggression in emerging adults (Little & Seay, 2014). In addition, a recent longitudinal study which assessed paternal and maternal psychological control simultaneously by employing a regression analysis found that only fathers' psychological control significantly contributed to externalising and internalising problems in adolescent children (Lansford, Laird, Pettit, Bates, & Dodge, 2014) further emphasising the paternal role in children's behavioural and emotional development.…”
Section: Discussionsupporting
confidence: 88%
“…Although the vast majority of research in the area is predominantly focused on maternal parenting style (Cabrera, Tamis-LeMonda, Bradley, Hofferth, & Lamb, 2000;Simons & Conger, 2007) current results are in line with several studies which found that paternal but not maternal authoritarian parenting practices including psychological control are linked to increased relational aggression in children (Nelson & Crick, 2002;Nelson, Hart, Yang, Olsen, & Jin, 2006) and to relational and overt aggression in emerging adults (Little & Seay, 2014). In addition, a recent longitudinal study which assessed paternal and maternal psychological control simultaneously by employing a regression analysis found that only fathers' psychological control significantly contributed to externalising and internalising problems in adolescent children (Lansford, Laird, Pettit, Bates, & Dodge, 2014) further emphasising the paternal role in children's behavioural and emotional development.…”
Section: Discussionsupporting
confidence: 88%
“…adults may use relational aggression to gain control or in selfdefense against rejection and conditional acceptance, which may evoke feelings of distrust, resentment, or alienation and cultivate poorer friendships (Grotpeter & Crick, 1996). Similarly, social information processing theory suggests that emerging adults who experience parental psychological control may be more likely to perceive hostility in peer interactions and thus respond with relational aggression (Little & Seay, 2014). Notably, our finding that college students' relational aggression mediates the relation between perceived parental psychological control and students' friendship quality should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Relational aggression refers to manipulative social behaviors such as gossiping, threatening friendships, and social exclusion that may increase peer rejection and damage friendship quality (Crick, 1996). As previous research has found links between parental psychological control and relational aggression during emerging adulthood (Clark et al, 2015;Little & Seay, 2014), psychological control may indirectly affect emerging adults' friendship quality through the transmission of manipulative interaction styles like relational aggression. Thus, the present study investigates the role of parental psychological control in college students' friendship quality and use of relational aggression with peers.…”
mentioning
confidence: 99%
“…Indirectly, the child may witness his or her parents, siblings, and peers acting aggressively toward other people, which then serves as modeling behavior for the child's own social relationships (Stauffacher & DeHart, 2006). Previous cross-sectional and longitudinal studies (Little & Seay, 2014;Vaillancourt, Miller, Fagbemi, Côt e, & Tremblay, 2007) have shown that higher levels of parental warmth and monitoring, and lower levels of parental hostility, are associated with less physical and relational aggression (Kawabata et al, 2011). Warm parents who are high in monitoring provide children with a safe environment that allows them to learn positive social relationship skills, whereas hostile parents provide children with a harmful environment that leads them to learn destructive ways of interacting with others.…”
Section: The Role Of Parents Siblings and Peers In The Development mentioning
confidence: 99%